거대세포바이러스 감염에 의한 소장폐색 - 나양원(Yang Won Nah); 서재희(Jae-Hee Suh); 김성숙(Sung Sook Kim); 김도하(Do Ha Kim); 박능화(Neung Hwa Park); 조홍래(Hong Rae Cho); 최대화(Dae Hwa Choi); 고병균(Byung Kyun Ko); 남창우(Chang Woo Nam); 김규열(Gyu Yeol Kim); 박건춘(Kun Choon Park) (Annals of surgical treatment and research, 2002)
The human cytomegalovirus (CMV), a member of the herpes virus family, can cause a lifelong infection with episodes of endogenous reactivation. Almost the entire adult Korean population has been infected with CMV; they have serum CMV antibodies of IgG class. Reactivation is clinically silent in immunocompetent individuals. Symptomatic illness, such as pneumonitis, retinitis, hepatitis or gastroenteritis, is usually confined to immunocompromized patients. The colon, stomach and esophagus are the organs frequently infected with CMV in these patients. A CMV infection may also complicate an inflammatory bowel disease. CMV enteritis involving the small bowel, which makes up less than 10% of the CMV gastroenteritis cases, usually presents with diarrhea, bleeding and perforation, but rarely evokes obstruction. The authors experienced a case of CMV enteritis of the terminal ileum, presenting as an intestinal obstruction, which developed in an immunocompetent individual with no underlying disease. This appears to be a world first. (J Korean Surg Soc 2002;62:512-516) KCI Citation Count: 2